Biomarqueurs métabolomiques en relation avec les problèmes de comportement auprès de jeunes Inuit du Nunavik - St-Jean, Audray (Université Laval, 2016)
Obesity and insulin resistance are associated with mood disorders and elevated plasma concentrations of branched-chain amino acids (BCAAs: isoleucine, leucine and valine), and aromatic amino acids (AAAs: phenylalanine and tyrosine). Because AAAs are precursors of key neurotransmitters and their uptake into the brain is competitive with respect to the uptake of BCAAs via their transport through the same carrier, we explored the relationship between metabolomic biomarkers (BCAAs and AAAs) and behavioral problems among young Inuit from Nunavik. The current analysis includes 141 youth who participated in the Nunavik Child Development Study baseline (2005-2010) and adolescent follow-up (2013-2015). BCAA and AAA plasma concentrations were measured at baseline and categorised in tertiles of the ratio of BCAAs to AAAs (BCAA/AAA). Behavioral problems were assessed during adolescence with the Youth Self-Report (YSR) from the Child Behavior Checklist (CBCL). The relationship between tertiles of BCAA/AAA and mean scores of YSR syndromes was assessed with general linear models. We noted a trend toward a higher mean scores of internalizing problems (Ptrend=0.05) and somatic complaints (Ptrend=0.01) syndromes with higher BCAA/AAA ratio. No statistically-significant relationship was noted for externalizing and attention problems scores. We observed higher (Ptrend < 0.05) internalizing problems and somatic complaints syndrome scores with a higher ratio of BCAA/AAA among normal weight participants, but not among overweight or obese. Our results suggest that an elevated BCAA/AAA ratio is associated with behavioral problems among youth, mainly internalizing problems. L’obésité et la résistance à l’insuline sont associées avec les troubles de l’humeur ainsi que des concentrations plasmatiques élevées en acides aminés ramifiés (BCAAs : isoleucine, leucine et valine) et en acides aminés aromatiques (AAAs : phénylalanine et tyrosine). Étant donné que les AAAs sont des précurseurs de neurotransmetteurs clés et que leur apport au ...